Generational Diversity as an Important Factor of Success in Implementing the Fourth Industrial Revolution - Beata HYSA; Anna MULARCZYK (Communications of International Proceedings, 2021)
Industry 4.0. requires companies to transform their technology, process, and organization through advanced use of digital solutions and data resources. At the same time, generational changes are forcing cultural changes in the workplace and how employees are managed. To thrive in the Industry 4.0 ecosystems, organisations will need to ensure a sufficient number of skilled workers, keeping in mind that the workforce will have to undergo frequent and continuous change. The article's main purpose is to present the importance of managing employees of different generations as an important element in the implementation of Industry 4.0. The research methodology is based on the analysis of Eurostat demographic data. The results confirmed the hypothesis that in Poland, as well as in European Union countries, there is an ageing of society which will affect the participation of particular generations in the labour market. The forecast developed in the paper can be used to change employment strategies. Proper recognition of the direction and distribution of generational change can also help determine how to manage employees and establish incentive systems.
Keywords: Industry 4.0; generational diversity; ageing population